Amino acid storage: lysosomal double role in health and disease - Aiswarya Raj; Samantha Shrihari; Urmi Bandyopadhyay (Autophagy Reports)
Cellular homeostasis depends on a multitude of cellular functions, which in turn depend on the clearance of damaged components for their maintenance. Lysosomes being one of the main sites of recycling, are at the frontline for cellular protein degradation, which leads to generation of protein building blocks, the amino acids (AAs), within the lysosomal lumen. However, the fate of these lysosomal pool of AAs are only partly known. Recently, studies from our and other groups have led to the finding that AA can be stored in lysosomes and revealed a homeostatic communication of these storages with the environment. Thus, lysosome appear to be a nutritional signaling hub that has a dual role. As a degradation-competent hydrolytic sack, lysosomes have a long-studied degradative function, additionally now they can either store or channel into utilization of the AAs generated through their proteolytic activity. Since the existence of a lysosomal AA storage pool has been determined by changing the levels of extracellular AAs, this indicates a multi-directional homeostatic communication between the lysosome and the extracellular environment. This Lysosomal homeostatic and adaptive response to the niche could be vital for life-threatening age-related degenerative disorders, where the lysosome-autophagy pathway and the microenvironmental cues play major roles in the disease progression, which will be discussed further in this piece.